Seventh Five Year Plan 1985-90 Draft Annual Plan for 1987-88 Volume—I Introduction, Sectoral Review and Statements Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1985)
This being a Union Territory (without Legislature) directly administrated by the Central Government all the expenditure on Plan activities is met directly by the Centre. Likewise, the receipt of the territory forms part of the receipt of the Government of India. Beside the area grant in respect of the Administration’s expenditure, expenditure of capital nature is entirely met out of the appropriate grant of the Centre.
Andaman and Nicobar Administration